(untitled) (Al Dzahab, 2023)
Purpose: This study aims to determine the effect of service quality and public service motivation on community satisfaction on employees of Terminal Type A Kiliran Jao. Design/methodology/approach: The method used in this research is quantitative research with a descriptive approach. The population in this study were employees at Terminal Type A Kiliran Jao. The sample used was 84 people using a saturated sampling technique (census). The data analysis technique is multiple linear regression. Findings: The results of the study show that: (1) Service quality has a positive and significant effect on community satisfaction. (2) Public service motivation has a positive and significant effect on community satisfaction. (3) Quality of service and motivation of public services together have a positive and significant effect on community satisfaction in Terminal Type A Kiliran Jao. Research implications: The results of this study concluded that with good service quality and high motivation for public services, especially in the type A terminal, Kiliran Jao can increase people’s satisfaction in using the terminal.